Tackling the politics of intersectoral action for the health of people and planet - Buse, Kent; Tomson, Goran; Kuruvilla, Shyama; Jemilah, Mahmood *; Alden, Anastasia; van der Meulen, Maarinke; Ottersen, Ole Petter; Haines, Andy (BMJ Publishing Group, 2022)
Human activities are wreaking extensive damage on the natural systems of the planet and undermining the prospects for the health of current and future populations. The 2021 report of the Intergovernmental Panel on Climate Change provided further evidence of the increasing urgency of responding to the threats posed by climate change—which the UN secretary general labelled “a code red for humanity.”12